Big Research Questions about the Human Condition : a Historian's Will - Jarrick, Arne (Anthem Press, 2020)
Ask bigger, fewer, and clearer questions! This is the major message of this book, comprising a set of issues to focus on, hereby suggesting a way to overcome the fragmentation characterising the humanities today. It also urges humanists to regard humanities research as an integral part of science, although uniquely dealing with humans as decision making, meaning seeking and self-reflecting agents.